2018
DOI: 10.1155/2018/2905141
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Pore Structure Characterization and Permeability of Mudrocks and Fine-Grained Sandstones in Coal Reservoirs by Scanning Electron Microscopy, Mercury Intrusion Porosimetry, and Low-Field Nuclear Magnetic Resonance

Abstract: Porosity and permeability of two typical sedimentary rocks in coal bearing strata of underground coal mines in China, i.e., mudrocks and fine-grained sandstones, were comprehensively investigated by multiple experimental methods. Measured porosity averages of the helium gas porosity ( ), MIP porosity ( MIP ), water porosity ( ), and NMR porosity ( NMR ) of the twelve investigated rock samples range from 1.78 to 16.50% and the measured gas permeabilities ( ) range from 0.0003 to 2.4133 mD. Meanwhile, pore types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Note that the ordinate value of the starting point of each data set is 1. 8 Geofluids (approximately 2.15 to 3.15 GPa) of the mudstone significantly lower than the unloading modulus. As the confining pressure increases, more pore and microcrack compressions occur during the exertion of the confining pressure; therefore, the irreversible strain in this stage decreases and the secant modulus increases slightly with the increase in the confining pressure.…”
Section: Effect Of Confining Pressure On Deformation Mechanism and Pementioning
confidence: 89%
See 1 more Smart Citation
“…Note that the ordinate value of the starting point of each data set is 1. 8 Geofluids (approximately 2.15 to 3.15 GPa) of the mudstone significantly lower than the unloading modulus. As the confining pressure increases, more pore and microcrack compressions occur during the exertion of the confining pressure; therefore, the irreversible strain in this stage decreases and the secant modulus increases slightly with the increase in the confining pressure.…”
Section: Effect Of Confining Pressure On Deformation Mechanism and Pementioning
confidence: 89%
“…Therefore, mudstone formations are an effective barrier to geofluid accumulation and play an important role in petroleum systems and in deep energy and waste disposals. Although not always the case, the permeability of mudstones in a well-compacted and undisturbed state is less than 1 μD (≈10 -18 m 2 ) based on laboratory measurements of intact mudstone samples [3][4][5][6][7][8][9]; the reason for this result is that mudstone is rich in fine-grained and clay sediments and usually has a mean pore radius of less than 100 nm [4,10,11], which is more than several orders of magnitude smaller than that of coarser-grained rocks such as sandstone that retains geofluids [12,13]. Since the clay grains are platy shaped, mudstone has higher compressibility than other sedimentary rocks and its permeability, which is related to porosity, decreases greatly with increasing diagenesis depth or consolidation pressure [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…NMR has been widely used for the characterization of complex porous media, such as the petroleum reservoir rocks and coal [32][33][34][35][36]. For example, a recent research by Zhang et al demonstrated that the successful use of the NMR to obtain pore size distribution of mudrock and fine-grained sandstone samples [37]. When the magnetic field is small, few paramagnetic minerals within the coal could influence the measured results and the magnetic information on solid state proton ( 13 C and 1 H) can be shielded [31,38].…”
Section: Nmr Measurementsmentioning
confidence: 99%
“…Coal with extremely complex pore structure can store a large amount of CSG; CSG has also become an energy resource of global significance. In addition to USA, countries such as Canada, Australia, China, and India practice CSG drainage activities [5][6][7][8][9][10]. In Australia, the CSG drainage industry is growing rapidly and is becoming one of the significant energy sources in both Queensland [6,11] and New South Wales [5].…”
Section: Introductionmentioning
confidence: 99%